PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 034 TELUK MEGA KECAMATAN TANAH PUTIH - Yatik '; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the students achievment of science studies SD Negeri 034 Teluk Mega fifth graderes still low with an average value of 60,75 and minimum completenness criteria (KKM) science studies is 70,00. Between students, amounting to 20 people only 9 students who achieve classical KKM with 45,00%. This research is Classroom Action Research (CAR), wich aims to improve the student achievement of science studies class fifth at SD Negeri 034 Teluk Mega Kecamatan Tanah Putih with implementation of model cooperative learning thype Group Investigation. Formulation of the problem: is the implementation of model cooperative learning thype Group Investigation can improve students achievment of science studies at SD Negeri 034 Teluk Mega fifth graderes?. The research was conducted on April to May 2016 by 2 cycles. Subjects were students of SD Negeri 034 Teluk Mega fifth graderes, totalling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. Activities of the teacher in the learning process in cycle I the first meeting to 58,33% and the second meeting improve to 66,67%. Cycle II first meeting and the second meeting improve 83,33% and the second meeting improve to 95,83%. Result of data analysis of students activities in the first meeting cycle I with the first meeting of an avarage of 54,17% and a second meeting improve to 62,50%. Cycle II first meeting improve 79,17% and the second meeting improve to 95,83%. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 60,75. In the first cycle improve an average of 70,00 with increase big as 15,22% and an impove in the second with an average of 82,50 with increase big as 35,8%. Result in the class fifth at SD Negeri 034 Teluk Mega that the implementation of model cooperative learning thype Group Investigation can improve students achievement of science studies at fifth graderes SD Negeri 034 Teluk Mega. Key Word: Kooperative Learning, Group Investigation, Result Of Science Studies